Applying english grammar. : corpus and functional approaches - Coffin, Caroline; Hewings, Ann.; O'Halloran, Kieran (London Routledge, 2011)
This edited collection is about the application of English grammar and specialises in 'functional' and'corpus' approaches, approaches which are increasingly recognised as providing significant insights into English language in action. It aims to stimulate interest and understanding of grammar as an applied tool not just for grammarians or language learners, but for all those interested in how language is organized to shape our view of events in the world. As the chapters in this book show, functional and corpus approaches allow us to make observations that would not be amenable through more traditional forms of grammatical analysis. They also illustrate how researchers can fruitfully bring together corpus and functional approaches to reveal how grammar and lexis create and transmit values, identities and ideologies. Research in Critical Discourse Analysis (CDA) has a long tradition of drawing on functional grammar but has only relatively recently begun to draw on corpus linguistics. As such, the book is unusual in presenting work on CDA which draws on corpus linguistics. But not only that, it is also unique in presenting work in CDA which brings together the methodologies of corpus linguistics and functional grammar, demonstrating their combined potential for illuminating ideological perspectives, particularly in media texts. Given this focus and given the increasing value of empirical data, the book will be of interest to those in a range of disciplines including the humanities and media and cultural studies. Chapters comprise both newly commissioned and previously published works that illustrate the two methodological approaches to grammatical analysis and how they can be applied to deepen our understanding of language.